Biodistribution and Efficacy of Human Adipose-Derived Mesenchymal Stem Cells Following Intranodal Administration in Experimental Colitis - Lopez-Santalla, Mercedes; Mancheño-Corvo, Pablo; Escolano, Amelia; Menta, Ramon; DelaRosa, Olga; Abad, Jose Luis; Büscher, Dirk; Redondo, Juan M.; Bueren, Juan A.; Dalemans, Wilfried; Lombardo, Eleuterio; Garin, Marina I. (Frontiers in Immunology, 2017)
Mesenchymal stem cells (MSCs) have a large potential in cell therapy for treatment of inflammatory and autoimmune diseases thanks to their immunomodulatory properties. The encouraging results in animal models have initiated the translation of MSC therapy to clinical trials. In cell therapy protocols with MSCs, administered intravenously, several studies have shown that a small proportion of infused MSCs can traffic to the draining lymph nodes (LNs). This is accompanied with an increase of different types of regulatory immune cells in the LNs suggesting the importance of migration of MSCs to the LNs in order to contribute to immunomodulatory response. Intranodal (IN), also referred as intralymphatic, injection of cells, like dendritic cells, is being proposed in the clinic for treatment of cancer and allergy, showing that this route of administration is clinically safe and efficient. In this study, we investigated, for the first time, the biodistribution and the efficacy of Luciferase+ adipose-derived MSCs (Luci-eASCs), infused through the inguinal LNs (iLNs), in normal mice and in inflamed mice with colitis. Most of the Luci-eASCs remain in the iLNs and in the adipose tissue surrounding the inguinal LNs. A small proportion of Luci-eASCs can migrate to other locations within the lymphatic system and to other tissues and organs, having a preferential migration towards the intestine in colitic mice. Our results show that the infused Luci-eASCs protected 58% of the mice against induced colitis. Importantly, a correlation between the response to eASC treatment and a higher accumulation of eASCs in popliteal, parathymic, parathyroid and mesenteric LNs were found. Altogether, these results suggest that IN administration of eASCs is feasible and may represent an effective strategy for cell therapy protocols with human adipose-derived mesenchymal stem cells in the clinic for treatment of immune-mediated disorders.